2012
DOI: 10.1063/1.4743415
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation and photochemistry of V+(H2O)n, n = 1–4, in the 360–680 nm region

Abstract: The photodissociation and photochemistry of V + (H 2 O) n , n = 1-4, was studied in the 360-680 nm region in a Fourier transform ion cyclotron resonance mass spectrometer. The light of a high pressure mercury arc lamp was filtered with band pass filters, with center wavelengths from 360 to 680 nm in steps of 20 nm. The bandwidth of the filters, defined as full width at half maximum, was 10 nm. Photodissociation channels are loss of water molecules, as well as loss of atomic or molecular hydrogen, which may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
2
15
0
3
Order By: Relevance
“…In Gasphasenclustern zeigen mehrere Systeme Wasserstoffentwicklung unter dem Einfluss der Schwarzkörperstrahlung bei Raumtemperatur, [5] insbesondere Mg + (H 2 O) n , [6] Al + (H 2 O) n [7, 8] und V + (H 2 O) n [9] . Die photochemische Wasserstoffbildung wurde auch für Mg + (H 2 O) n [10] und V + (H 2 O) n untersucht [11] . Die Bildung von H 2 aus Al + (H 2 O) n , die durch Schwarzkörperstrahlung aktiviert wird, zeigt eine interessante Größenabhängigkeit, [7, 8] die einige Hinweise auf mögliche Mechanismen gab.…”
Section: Figureunclassified
See 1 more Smart Citation
“…In Gasphasenclustern zeigen mehrere Systeme Wasserstoffentwicklung unter dem Einfluss der Schwarzkörperstrahlung bei Raumtemperatur, [5] insbesondere Mg + (H 2 O) n , [6] Al + (H 2 O) n [7, 8] und V + (H 2 O) n [9] . Die photochemische Wasserstoffbildung wurde auch für Mg + (H 2 O) n [10] und V + (H 2 O) n untersucht [11] . Die Bildung von H 2 aus Al + (H 2 O) n , die durch Schwarzkörperstrahlung aktiviert wird, zeigt eine interessante Größenabhängigkeit, [7, 8] die einige Hinweise auf mögliche Mechanismen gab.…”
Section: Figureunclassified
“…[9] Die photochemische Wasserstoffbildung wurde auch für Mg + -(H 2 O) n [10] und V + (H 2 O) n untersucht. [11] Die Bildung von H 2 aus Al + (H 2 O) n , die durch Schwarzkçrperstrahlung aktiviert wird, zeigt eine interessante Grçßenabhängigkeit, [7,8] die einige Hinweise auf mçgliche Mechanismen gab. Quantenchemische Berechnungen von Reinhard und Niedner-Schatteburg [12] sowie Ab-initio-Moleküldynamik-Simulationen von Siu und Liu [13] [15] was das Vorhandensein der Hydrid-Hydroxid-Struktur HAlOH + (H 2 O) nÀ1 unterstützt.…”
unclassified
“…Studying hydrated metal ions in the gas phase provides the opportunity to investigate solvation at a molecular level and to study various chemical processes such as hydrogen production via catalysis at metal centers [32] and corrosion effects [33] in a welldefined environment. Our group has an extended history in studying these systems [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Infrared action spectroscopy, coupled with quantum chemical calculations, is a powerful technique used to investigate the structures of gas-phase molecular complexes, [52][53][54][55][56][57][58][59][60] in particular hydrated metal ions [61][62][63][64][65][66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%
“…In gas‐phase clusters, several systems show hydrogen evolution upon exposure to room‐temperature black‐body radiation, [5] in particular Mg + (H 2 O) n , [6] Al + (H 2 O) n , [7, 8] and V + (H 2 O) n [9] . Photochemical hydrogen formation has also been studied for Mg + (H 2 O) n [10] and V + (H 2 O) n [11] . The formation of H 2 from Al + (H 2 O) n activated by black‐body radiation exhibits an intriguing size dependence, [7, 8] which gave some hints on possible mechanisms.…”
Section: Figurementioning
confidence: 99%
“…[9] Photochemical hydrogen formation has also been studied for Mg + (H 2 O) n [10] and V + (H 2 O) n . [11] The formation of H 2 from Al + (H 2 O) n activated by black-body radiation exhibits an intriguing size dependence, [7,8] which gave some hints on possible mechanisms. Quantum chemical calculations by Reinhard and Niedner-Schatteburg [12] along with ab initio molecular dynamics simulations by Siu and Liu [13] revealed that the reaction takes place in two steps: First, a concerted proton transfer takes place through a water "wire" of at least three H 2 O molecules, from a first-shell water molecule to the other side of the Al + center, where the proton is reduced to hydride and simultaneously Al I is oxidized to Al III .…”
mentioning
confidence: 99%